Jezikovna realnost v Avstriji z vidika priseljencev in čezmejnih delavcev s slovenskim državljanstvom - Tibaut, Katarina (Dve domovini, 2023)
The article deals with the linguistic reality of Slovenian citizens in Austria who, by transferring their place of residence or place of work, enter a linguistically heterogeneous social space due to the official German language, its varieties, and other languages that are spoken there. The purpose of the research was to find out, on the one hand, which languages and linguistic genres Slovenian citizens use in their (working) daily life in Austria and, on the other hand, whether there are statistically significant differences between international migrants and cross-border workers. The study contributes a first sociolinguistic insight into a still largely unexplored topic.
Keywords: Austria; Avstrija; cross-border workers; čezmejni delavci; German language; international migrants; jezikovna praksa; language practice; nemščina; priseljenci; Slovenci; Slovenians; socioliguistics; sociolingvistika